Network characteristics of emotional resilience, anxiety, and depression among Chinese adolescents and their gender differences - Liu, Chang; Pi, Xiao-Xia; Liu, Bo; Zhang, Li; Luo, Meng-Ying; Zhang, Yu-Jun; Zhang, Xin-Feng; Nie, Suo-Cheng (Frontiers in Psychiatry, 2025)
ObjectiveTo explore the network structure of emotional resilience and anxiety-depressive symptoms in adolescents and identify gender differences in these networks.MethodA convenience sample of students from 21 middle schools in Jingzhou City was recruited for an online questionnaire survey. Emotional resilience, anxiety, and depression symptoms were assessed using the Adolescents’ Emotional Resilience Questionnaire, Generalized Anxiety Disorder Scale (GAD-7), and Patient Health Questionnaire (PHQ-9), respectively. Network analysis was performed to construct a model of emotional resilience dimensions (GP: generate positive emotion, RN: recover from negativity) and anxiety-depressive symptoms, with key features identified via expected influence (EI) and bridge expected influence (bEI). Gender differences were tested using the Network Comparison Test.ResultsA total of 17,499 adolescents were included. The prevalence of anxiety (GAD-7 ≥ 10) was 7.43% in males and 13.32% in females; depression (PHQ-9 ≥ 10) prevalence was 9.89% in males and 16.33% in females. Core symptoms included “uncontrollable worry,” “depressed mood,” and “psychomotor problems,” while four bridge symptoms were identified: “GP,” “RN,” “restlessness,” and “depressed mood. “ Network structure (M=0.144, p < 0.001) and global strength (S=0.354, p < 0.001) differed significantly by gender.ConclusionAdolescents need to develop emotional resilience in a balanced manner, and targeted interventions on core (e.g., “uncontrollable worry”, “psychomotor problems”) and bridge symptoms (e.g., “GP,” “RN,” “restlessness” and “depressed mood”) in the context of anxiety and depression are crucial for preventing these conditions in youth.